2006
DOI: 10.1186/1471-2466-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Living with primary ciliary dyskinesia: a prospective qualitative study of knowledge sharing, symptom concealment, embarrassment, mistrust, and stigma

Abstract: BackgroundPrimary ciliary dyskinesia (PCD) is a chronic respiratory disease for which there is little psycho-social research and no qualitative studies of individuals living with the condition. A questionnaire-based survey in 2003 found evidence of stigmatisation in some individuals with PCD. Although the questionnaire had face and construct validity, stigmatisation was not cross-validated against interviews. The present study had the twin aims of carrying out a qualitative study of the adult patients living w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…This is expected to increase shared knowledge, decrease mistrust of general practitioner who is generally poorly informed of what is a rare disease, and possibly to facilitate early diagnosis [30]. There is also the need for support from peer groups and volunteers to diminish stigmatisation and to give practical help to patients with PCD and to their families.…”
Section: Discussionmentioning
confidence: 99%
“…This is expected to increase shared knowledge, decrease mistrust of general practitioner who is generally poorly informed of what is a rare disease, and possibly to facilitate early diagnosis [30]. There is also the need for support from peer groups and volunteers to diminish stigmatisation and to give practical help to patients with PCD and to their families.…”
Section: Discussionmentioning
confidence: 99%
“…However, the item used in this study addresses an important dimension of stigma that is particularly relevant to the context of blogging about health. Both theory (Goffman, 1963;Scambler & Hopkins, 1986) and the results of research (Gray, 2002;Snadden & Brown, 1991;Whalley & McManus, 2006) identify shame and embarrassment as being central to the experience of stigma. Moreover, items addressing shame and embarrassment are pervasive in measures of health-related stigma; at least 10 different measures of stigma specific to particular health conditions (e.g., HIV, epilepsy, etc.)…”
Section: Limitationsmentioning
confidence: 92%
“…In his work on stigma, Goffman (1963, p. 7) notes that "shame becomes a central possibility, arising from the individual's perception of one of his [or her] own attributes as being a defiling thing to posses." Qualitative research also offers evidence that embarrassment is a central element of stigma among people coping with a range of health conditions such as primary ciliary dyskinesia (Whalley & McManus, 2006) and asthma (Snadden Downloaded by [UNAM Ciudad Universitaria] at 11:37 22 December 2014& Brown, 1991, as well as among parents of autistic children (Gray, 2002). Embarrassment and shame concerning one's self-with-illness is a particularly important dimension of stigma to consider.…”
mentioning
confidence: 97%
“…To date, few studies have reported the psychological and social burden of PCD . Qualitative studies have shown the emotional impact of PCD, with prominent themes arising including anger and frustration on account of the constant symptoms, treatment burden, and anxiety about their future health .…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies have shown the emotional impact of PCD, with prominent themes arising including anger and frustration on account of the constant symptoms, treatment burden, and anxiety about their future health . Feelings of embarrassment were attributed to the need to cough, expectorate sputum, or blow nose in social settings . In the absence of disease‐specific questionnaires, researchers have used generic HRQoL measures to investigate the psycho‐social impact of PCD including the Wechsler intelligence scale for children, the child behavior check‐List questionnaire, St George's respiratory questionnaire, Leicester cough questionnaire, and medical outcomes study short form 36 .…”
Section: Discussionmentioning
confidence: 99%